Technology-Assisted Inductive Learning: A Content Analysis of Prospective Mathematics Teachers' Lesson Plan - Wulandari, Enika; Sukestiyarno, YL; Scholastika, Mariani; Masrukan, Masrukan (Edumatica : Jurnal Pendidikan Matematika, 2025)
The shift in learning paradigm from passive to active requires prospective teachers to design meaningful learning experiences, one of which is through a technology-assisted inductive approach. This study aims to analyze the content of lesson plans developed by prospective mathematics teachers to implement technology-supported inductive learning. Using a qualitative content analysis method, this study involved 15 prospective mathematics teacher students from the State Islamic University of Salatiga who had taken courses related to lesson planning. The data sources for this study were lesson plan documents based on inductive learning, including Problem-Based Learning and Discovery Learning. Data were analyzed using thematic analysis to identify hidden patterns and themes. The results show that prospective teachers have integrated technology into each indicator of inductive learning, where the learning stages clearly begin from specific cases or problems to the generalization of concepts. This study contributes to providing an in-depth understanding of how prospective mathematics teachers translate inductive learning theory into lesson planning practices in the digital era, while also identifying aspects that need improvement in teacher training. Future research should investigate the relationship between the quality of lesson plan design and classroom teaching performance. Furthermore, comparative studies involving different technology platforms are needed to identify which tools best facilitate the conceptual discovery phase of inductive learning.